Residual deflection analysis in negative moment regions of steel-concrete composite beams under fatigue loading. (15th January 2018) - Song, Aiming; Wan, Shui; Jiang, Zhengwen; Xu, Jie
Highlights: The fatigue deformation behavior of steel-concrete composite beams under negative moment was investigated. A prediction model of residual deflection related to pre-cracked loading was proposed. An analytical model of residual deflection related to fatigue loading was proposed. Abstract: This paper presents the results of an experimental and analytical study on the residual deflection behavior in the negative moment regions of steel-concrete composite beams under fatigue loading. Firstly, fatigue tests with different load amplitudes were performed on two steel-concrete composite plate beam specimens subjected to negative moment. The residual values of slip and deflection at the interval time of the loading procedure were measured by laser displacement sensors. To study the development law of residual deflection under fatigue loading, the total residual deformation fN is then regarded as the superposition of the plastic deflection f 1 related to pre-cracking loading and the residual deflection fi related to fatigue loading. The analytical models of f 1 and fi are presented based on the existing research results of previous researchers. Finally, the applicability and accuracy of the proposed analytical model are validated through the comparison between modeling results and the data of the experimental beams performed in this study and reported in the earlier companion paper. The fatigue design recommendations for the steel-concrete composite beams subjected to negative moment were given based on the fatigue test and model analysis.